LEGAL PROTECTION OF REGISTERED TRADEMARK OWNERS’ ECONOMIC RIGHTS AGAINST THE ALLEGED DISTRIBUTION OF COUNTERFEIT DANCOW MILK PRODUCTS - Mhd Al Amin Bintang; Aida Nur Hasanah (Journal Analytica Islamica, 2026)
The circulation of suspected counterfeit Dancow-branded milk products through e-commerce platforms raises concerns regarding the protection of the economic rights of registered trademark owners in the digital marketplace. This study aims to analyze violations of trademark owners’ economic rights arising from the unauthorized use of registered trademarks and to examine the available civil legal remedies under Law Number 20 of 2016 concerning Trademarks and Geographical Indications, as well as from the perspective of the Indonesian Ulema Council (MUI) Fatwa Number 1 of 2005 on the Protection of Intellectual Property Rights. This research employs a normative-juridical method using statutory and conceptual approaches. The results indicate that the circulation of products suspected of bearing counterfeit Dancow trademarks may infringe the exclusive rights of registered trademark owners and potentially cause economic losses, including reduced commercial value, loss of business opportunities, and reputational harm. The Trademark Law provides civil remedies through claims for damages and requests to cease the circulation of infringing goods, supported by general provisions on unlawful acts and the legal responsibilities of e-commerce platform operators. From the perspective of Islamic law, the unauthorized use of another party’s trademark is prohibited because it violates the principles of justice and the protection of property rights. This study contributes to strengthening the legal protection of registered trademark owners’ economic rights by integrating positive law and Islamic law within the context of digital commerce.